2009
DOI: 10.3389/neuro.06.019.2009
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-processing interneurons in the honeybee brain

Abstract: The afferents of the Johnston's organ (JO) in the honeybee brain send their axons to three distinct areas, the dorsal lobe, the dorsal subesophageal ganglion (DL-dSEG), and the posterior protocerebral lobe (PPL), suggesting that vibratory signals detected by the JO are processed differentially in these primary sensory centers. The morphological and physiological characteristics of interneurons arborizing in these areas were studied by intracellular recording and staining. DL-Int-1 and DL-Int-2 have dense arbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Interestingly, if only the antennal articulations were free of wax, bees could detect vibrations and were able to discriminate and learn electrical cues to some extent. Electrophysiological recordings of the mechanosensory neurons in the Johnston's organ, a structure located in the second antennal segment involved in detecting acoustic vibrations (Ai, 2010), confirmed that electric stimulation induces neuronal responses. Therefore, much in the same way as body hairs are thought to contribute to human electric field perception (Chapman et al, 2005), passive antennal deflection caused by electrical stimulation may activate mechanosensory organs responsible for electroreception in bees.…”
mentioning
confidence: 81%
“…Interestingly, if only the antennal articulations were free of wax, bees could detect vibrations and were able to discriminate and learn electrical cues to some extent. Electrophysiological recordings of the mechanosensory neurons in the Johnston's organ, a structure located in the second antennal segment involved in detecting acoustic vibrations (Ai, 2010), confirmed that electric stimulation induces neuronal responses. Therefore, much in the same way as body hairs are thought to contribute to human electric field perception (Chapman et al, 2005), passive antennal deflection caused by electrical stimulation may activate mechanosensory organs responsible for electroreception in bees.…”
mentioning
confidence: 81%
“…This neuron has arborizations in the ipsilateral PPL, contralateral PPL and dSEG (Figure 7A,B) [44]. This neuron did not respond to the 265 Hz vibration, but responded instead to vibrations with long-lasting excitation during olfactory stimulation to the contralateral antenna (Figure 7C) [45].…”
Section: Vibratory Communication Of Honeybeesmentioning
confidence: 99%
“…Moreover studies using a honeybee standard brain (HSB) [46] found that DL-Int-1 was close to JO afferents in the center of the DL, while DL-Int-2 was close to JO afferents in the anterior region of the DL [44]. DL-Int-1 shows on-off phasic excitation or tonic inhibition to vibration stimuli at 265 Hz, while DL-Int-2 shows tonic excitation to vibration at 265 Hz [43].…”
Section: Neural Circuits Of Vibration Processingmentioning
confidence: 99%
“…5 that vision is also traveling via frequencies. Some researchers recently highlighted that odor is a vibration too (Ai 2010).…”
Section: The Right Vibesmentioning
confidence: 99%